The feasibility of two new anthropometric indices to identify hypertension in rural China: A cross-sectional study. Issue 44 (November 2016) - Chang, Ye; Guo, Xiaofan; Guo, Liang; Li, Zhao; Li, Yuan; Sun, Yingxian
Abstract : Abstract: Recently, 2 new anthropometric indices, the A Body Shape Index (ABSI) and Body Roundness Index (BRI), have been developed. Our study was to compare the associations between different anthropometric indices, including ABSI, BRI, body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR), and hypertension in a rural population of northeast China. This cross-sectional study was conducted in the rural areas of northeast China from January 2012 to August 2013 using a multistage, stratified random cluster-sampling scheme. All eligible permanent residents aged ≥35 years (a total of 14, 016 individuals) in each village were invited to participate in the study. A final sample size of 11, 345 (5253 males and 6092 females) were included in this study. All the 5 anthropometric measures were positively correlated with hypertension. The prevalence of hypertension increased across quartiles for ABSI, BMI, BRI, WC, and WHR. Multivariable logistic regression analysis of the presence of hypertension for the highest quartile versus the lowest quartile of each anthropometric measure, showed that BRI had the largest values of ORs (OR: 3.49, 95% CI: 2.86–4.21 in men; OR: 3.06, 95% CI: 2.56–3.67 in women) and ABSI had the smallest ORs (OR: 1.30, 95% CI: 1.06–1.58 in men; OR: 1.19, 95% CI: 1.04–1.34 in women). BRI had the highest AROCs for hypertension (AROC: 0.65, 95% CI: 0.64–0.67 for men and AROC: 0.68, 95% CI: 0.67–0.70 for women), while ABSI had the lowest AROCs for hypertension (AROC: 0.60, 95% CI: 0.58–0.61 for men and AROC: 0.59, 95% CI: 0.58–0.61 for women). Our results showed that ABSI, BMI, BRI, WC, and WHR were all associated with hypertension. ABSI showed the weakest association with hypertension, while BRI showed potential for use as an alternative obesity measure in assessment of hypertension.